Whose Research Counts? Teacher Research and the Practitioner-Academic Divide. Issue 4 (2nd October 2021) - Martell, Christopher C.; Carney, Mary M.; Marin, Katherine Ariemma; Hashimoto-Martell, Erin A.
Abstract: Scholars have theorized about the growing movement of teacher research, where school-based practitioners engage in systematic examinations of their own work. They have argued that teacher research challenges relationships of knowledge and practice, as teacher-researchers are likely to ask different questions and offer different perspectives compared to university-based researchers. Synthesizing teacher research studies published in peer-reviewed journals across the content areas of mathematics, science, social studies, and literacy/language arts, this review compares the questions asked and the results reported on content area studies done by PreK–12 teacher- and university-based researchers. This review provides a critical examination of our understanding of classroom instruction and student learning, revealing the important potential of practitioner research to inform educational change.